Kenduri Rewang Adabi Tour with UMP students strengthens good relationship - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PAYA BESAR, 10 January 2023 - Over 500 Universiti Malaysia Pahang (UMP) students enjoyed a delicious lunch for free in conjunction with the Kenduri Rewang Adabi Tour Programme with UMP students at Masjid Universiti.